2011
DOI: 10.4236/psych.2011.25077
|View full text |Cite
|
Sign up to set email alerts
|

A Review Study on the Marriage and Relationship Research in Turkey

Abstract: The aim of this study is to examine the studies on marriage and relationship in Turkey.127 studies (82 research studies and 45 scale studies) published and unpublished between 1997-2008 were examined toprovide an overview for professionals about the marriage and relationship research done in Turkey. The studies were reviewed in terms of their general characteristics, conceptual frameworks and methods of investigation. The results were discussed and suggestions were given in terms of future directions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Another important trend is the publication in Englishlanguage journals of studies researching marital challenges for couples beyond the United States and Europe;, this makes it possible for people all around the world to become more familiar with challenges facing families living in other countries. For example, Güney (2011) compared 127 research studies about marital satisfaction done in Turkey and concluded that the data was drawn from samples of highly educated and higher socioeconomic status couples reporting higher level of marital satisfaction, and suggested that future studies should evaluate the ecological context for lower socioeconomic status couples in Turkey. Li-li (2008) investigated trends in martial satisfaction of immigrant daughters-in-law from rural settings to Shanghai, indicating a higher marital satisfaction for these women.…”
mentioning
confidence: 99%
“…Another important trend is the publication in Englishlanguage journals of studies researching marital challenges for couples beyond the United States and Europe;, this makes it possible for people all around the world to become more familiar with challenges facing families living in other countries. For example, Güney (2011) compared 127 research studies about marital satisfaction done in Turkey and concluded that the data was drawn from samples of highly educated and higher socioeconomic status couples reporting higher level of marital satisfaction, and suggested that future studies should evaluate the ecological context for lower socioeconomic status couples in Turkey. Li-li (2008) investigated trends in martial satisfaction of immigrant daughters-in-law from rural settings to Shanghai, indicating a higher marital satisfaction for these women.…”
mentioning
confidence: 99%